Ethanol regulation of adenosine receptor-stimulated cAMP levels in a clonal neural cell line: an in vitro model of cellular tolerance to ethanol. - Gordon, A S (1986)
The acute and chronic neurologic effects of ethanol appear to be due to its interaction with neural cell membranes. Chronic exposure to ethanol induces changes in the membrane that lead to tolerance to the effects of ethanol. However, the actual membrane changes that account for tolerance to ethanol are not understood. We have developed a model cell culture system, using NG108-15 neuroblastoma-glioma hybrid cells, to study cellular tolerance to ethanol. We have found that adenosine receptor-stimulated cAMP levels increased markedly upon acute exposure to ethanol. However, the cells became tolerant to ethanol, since chronically treated cells required ethanol to maintain normal adenosine-stimulated cAMP levels. Moreover, the cells appeared to be dependent on ethanol, as evidenced by reduced adenosine-stimulated cAMP levels in the absence of ethanol. Recovery occurred after ethanol was withdrawn. These cellular changes appear to parallel the clinical events of acute ethanol intoxication, tolerance, and dependence.